2000
DOI: 10.1046/j.1365-2583.2000.00193.x
|View full text |Cite
|
Sign up to set email alerts
|

DNA structures common for chironomid telomeres terminating with complex repeats

Abstract: Tandem repeats, 340 bp long, have been shown to terminate the chromosomes in Chironomus pallidivittatus and similar DNA may be used for this purpose by related insects. In view of the importance of Chironomus in telomere studies, representing in principle a third system after short repeats and Drosophila telomeric retrotransposons, we have investigated the related Chironomus dilutus, to learn what DNA structures are conserved at the chromosome ends. Interspersed subrepeats in the telomeric repeats, which conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 37 publications
0
38
0
Order By: Relevance
“…Further differences between the subtelomere sequences of Drosophila chromosomes have emerged, with that of 2R closely resembling 3R, whereas 2L and 3L show similar sequences (Abad et al 2004). Few other insect subtelomeric regions are known, e.g., for Chironomus flies (Saiga and Edström 1985;Rosen and Edström 2000) and a cricket (Kojima et al 2002), and they are highly repeated structures reminiscent of the apparent organization of the bee proximal telomeres with their extensive AluI repeats (Beye and Moritz 1995).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further differences between the subtelomere sequences of Drosophila chromosomes have emerged, with that of 2R closely resembling 3R, whereas 2L and 3L show similar sequences (Abad et al 2004). Few other insect subtelomeric regions are known, e.g., for Chironomus flies (Saiga and Edström 1985;Rosen and Edström 2000) and a cricket (Kojima et al 2002), and they are highly repeated structures reminiscent of the apparent organization of the bee proximal telomeres with their extensive AluI repeats (Beye and Moritz 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Despite these observations, no evidence for differential telomere maintenance on individual chromosomes has been found to date. How telomeres consisting of repeats such as those found in Chironomus are maintained remains unclear, with gene conversion or RT-based mechanisms being possible (Rosen and Edström 2000); in other systems recombination-based mechanisms have been implicated (Pardue and DeBaryshe 1999;Fajkus et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The telomeres of the midge Chironomus have been studied extensively. Its chromosome ends consist of 50 -200-kb blocks of complex satellite repeats, which are present at seven of eight chromosome tips [64 -68]; the tip of the telocentric fourth chromosome harbors instead the kinetochore and other types of repetitive sequences [68,69]. Different telomeres contain different subfamilies of repeats, but these subfamilies also show considerable variation in distribution at the same telomere among different individuals in the same stock [65,70].…”
Section: Species That Lack Telomerase-generated Repeatsmentioning
confidence: 99%
“…It has been shown for Chironomus pallidivittatus that 340 bp tandem repeats may extend to the very end of the chromosome (López et al 1996). Similar sequences are present in other chironomid species and are thus likely to be terminal: in Chironomus thummi, 176 bp (Carmona et al 1985), Chironomus tentans, 350 bp (Nielsen et al 1990), and Chironomus dilutus, 341 bp units (Rosén and Edström 2000). A transcript of telomeric repeats is present in chironomid salivary glands (Carmona et al 1985;Saiga and Edström 1985) and other tissues (Morcillo et al 1994) and has been observed near the chromosome ends in C. thummi salivary glands (Botella et al 1991).…”
Section: Introductionmentioning
confidence: 89%